The spectrum of ethicality - Henderson, Verne E. (Journal of business ethics, 1984)
Business ethics is the continuing process of re-defining the goals and rules of business activity. In times of rapid change, spurred equally by technological innovation within the business community and by societal expectations in the larger community, participants who share in that process of re-defining goals and rules should be sensitive to professional differences. Lawyers and executives, for instance, while seeking a common societal good, will utilize measurably different goals and methods based on differences in leadership style, accountability to constituents and client relationship generally. Because of these differences, definitions of what is ethical will vary as well, spread across a spectrum of ethicality.